Dependence of future mortality changes on global CO2 concentrations: A review. (May 2018) - Lee, Jae Young; Choi, Hayoung; Kim, Ho
Abstract: The heterogeneity among previous studies of future mortality projections due to climate change has often hindered comparisons and syntheses of resulting impacts. To address this challenge, the present study introduced a novel method to normalize the results from projection studies according to different baseline and projection periods and climate scenarios, thereby facilitating comparison and synthesis. This study reviewed the 15 previous studies involving projected climate change-related mortality under Representative Concentration Pathways. To synthesize their results, we first reviewed the important study design elements that affected the reported results in previous studies. Then, we normalized the reported results by CO2 concentration in order to eliminate the effects of the baseline period, projection period, and climate scenario choices. For twenty-five locations worldwide, the normalized percentage changes in temperature-attributable mortality per 100 ppm increase in global CO2 concentrations ranged between 41.9% and 330%, whereas those of total mortality ranged between 0.3% and 4.8%. The normalization methods presented in this work will guide future studies to provide their results in a normalized format and facilitate research synthesis to reinforce our understanding on the risk of climate change. Highlights: This study is the first to review 15 RCP scenario-based previous projection studies. This study performed a novel normalization to overcome the inter-study heterogeneity. 25 locations worldwide showed very diverse percentage changes in mortality. The mean modeling years and the projection results showed an inverse relationship.